A new Maxillariella (Orchidaceae: Maxillariinae) from Costa Rica and Panama - Bogarín Chaves, Diego Gerardo (2018)
Maxillariella prostrata, a new species from Costa Rica and Panama is described and illustrated. This species is similar to M. acervata but differs in having a prostrate habit, elliptic leaves up to 2 cm long, pseudobulbs with two unequal apical leaves, one larger and the other smaller, a red-spotted lip, the column apex entire, and the pollinarium made up of two small globose pollinia on an oblong stipe. Maxillariella prostrata also resembles M. dichaeoides from Ecuador and Peru but differs in having yellow to white flowers spotted with red, and the lip with a well-defined callus